The effect of benzyl amino purin (BAP) and indole butyric acid (IBA) concentrations on the growth of shoot and root of Cinchona ledgeriana Moens in vitro propagation - Joko Santoso (Research Institute for Tea and Cinchona, 2012)
A research to evaluate effect of concentration of BAP and IBA on growth of shoot and root of Cinchona ledgeriana Moens in vitro culture, was conducted at Biomolecullar Laboratory of Research Institute for Biotechnology of Plantation Crops, Bogor. Testing on the effect of IBA on shoot growth was conducted in a CRD with five treatments and replicated 15 times. The treatments were BAP at several concentrations: 1, 2, 3, 4, and 5 mg/l. MS media culture was used as basic media and BAP added were based on the concentration tested. The parameters measured were number of sproute explants, number of root and height of shoot. The effect of IBA on the growth root was conducted based in a CRD with five treatments and replicated 15 times. The treatments were IBA at several concentrations: 0,5; 1,0; 1,5; 2,0, and 2,5 mg/l. B5 media culture was used as basic media and IBA were added based on the concentration tested. The parameters measured were number of rooted plantlets, number of root and length of root. Result showed that: (1) the best effect of BAP on the inisiation of shoot growth was obtained from the treatment of 3 mg/l concentration of BAP wich sprouted at seven days. Shoot inisiation of all concentrations were occured at 14 days; (2) the best effect of BAP on number of sproute explants and shoot height were obtained from the treatment of 3 mg/l concentration of BAP; (3) at seven days after cultured, the treatments of 1,5; 2,0; and 2,5 mg/l consentration of IBA gave the better root inisiation. At 14 days, the better root inisiation were obtained from the treatments of 1,5 and 2,0 mg/l consentration of IBA; (4) the treatment of 2,0 mg/l consentration of IBA gave the best effect on the number as well as the length of main root.